Analýza výskytu a transmisívneho prenosu tularémie na Slovensku - Gurycová, D (Epidemiologie, mikrobiologie, imunologie, 1997)
The morbidity from tularaemia in Slovakia has since the epidemic incidence in the sixties a declining trend. The mean annual morbidity rate declined from 5.5 per 10(5) population in 1960-1969 to 0.3 in 1980-1994 and is markedly influenced by the incidence of tularaemia in the well known epidemic area in western Slovakia where in 1985 also the first cases of transmission of tularaemia by ticks were recorded in Slovakia. During the last decade (1985-1994) in Slovakia 126 cases were notified, out of them 96.8% in the western Slovakian region, more than half of the cases were recorded in the districts of Nitra and Nové Zámky. The analysis of the incidence of the disease in western Slovakia as compared with the previous decade (1975-1984) drew attention to marked changes in the epidemiology of tularaemia and a rise of the cases transmitted from other sources of infection than hares and by ectoparasites. Their ratio is almost 66%, from that 20.5% formed by cases transmitted by ticks (15.6%) and by other arthropods (4.9%). In the majority of patients with ticks in the case-history the ulceroglandular form of the disease was recorded (79%), with the primary affection at the site of the tick-bite, in the majority with lymphadenitis in the inguinal area (63.2%). The majority of the cases was recorded in summer, most frequently in occupational groups: pupils and students, forestry workers and mainly other occupations. The results of an epidemiological survey and data on the prevalence of for ticks infected with Francisella tularensis in the endemic area of Slovakia indicate that the tick-borne of tularaemia in humans Central European ecological conditions is probably more frequent than hitherto assumed.
Keywords: tularemie; Animals; Slovakia; Incidence; lidé; Slovenská republika; klíšťata; zvířata; Ticks; Arachnid Vectors; incidence; arachnida jako vektory; Tularemia; Humans